2003
DOI: 10.1063/1.1524707
|View full text |Cite
|
Sign up to set email alerts
|

Ion bombardment effects on microcrystalline silicon growth mechanisms and on the film properties

Abstract: The role of ions on the growth of microcrystalline silicon films produced by the standard hydrogen dilution of silane in a radio frequency glow discharge is studied through the analysis of the structural properties of thick and thin films. Spectroscopic ellipsometry is shown to be a powerful technique to probe their in-depth structure. It allows to evidence a complex morphology consisting of an interface layer, a bulk layer, and a subsurface layer. The ion energy has been tuned by codepositing series of sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 46 publications
3
78
1
Order By: Relevance
“…18 At the same time it has been shown that such attempts to increase the hydrogen content and improve the passivation quality can significantly alter the nanostructure of a-Si:H leading to void-rich material and in some cases cause irreversible damage at the interface. In this work we demonstrate PECVD conditions using high hydrogen dilution (200 sccm H 2 compared to 2.5 to 10 sccm SiH 4 ), low power density (∼0.05 W/cm 2 ), and relatively high deposition pressure (8 mbar) 20 that result in material close to the a-Si:H-to-µc-Si:H transition regime, passivating c-Si and achieving effective lifetimes (τ eff ) > 10 ms. As a result of the low power density and high deposition pressure the ion bombardment energy is decreased, 21 thereby minimizing possible damage on and just below the surface of the c-Si substrate while shifting the a-Si:H-to-µc-Si:H transition to higher dilutions and allowing to deposit amorphous silicon at extremely high dilution conditions. We show how the τ eff correlates to changes in the nanostructure of the material, which in turn is varied by changing the hydrogen dilution and substrate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…18 At the same time it has been shown that such attempts to increase the hydrogen content and improve the passivation quality can significantly alter the nanostructure of a-Si:H leading to void-rich material and in some cases cause irreversible damage at the interface. In this work we demonstrate PECVD conditions using high hydrogen dilution (200 sccm H 2 compared to 2.5 to 10 sccm SiH 4 ), low power density (∼0.05 W/cm 2 ), and relatively high deposition pressure (8 mbar) 20 that result in material close to the a-Si:H-to-µc-Si:H transition regime, passivating c-Si and achieving effective lifetimes (τ eff ) > 10 ms. As a result of the low power density and high deposition pressure the ion bombardment energy is decreased, 21 thereby minimizing possible damage on and just below the surface of the c-Si substrate while shifting the a-Si:H-to-µc-Si:H transition to higher dilutions and allowing to deposit amorphous silicon at extremely high dilution conditions. We show how the τ eff correlates to changes in the nanostructure of the material, which in turn is varied by changing the hydrogen dilution and substrate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A further increase in H 2 dilution results in a decrease of the layer thickness. The reason for such behavior may result from a trade off between deposition rate and the hydrogen desorption from the growing film [21]. In Figure 2b also is shown the structural composition of the interface layer as a function of H 2 flow rate.…”
Section: Epitaxial Filmsmentioning
confidence: 98%
“…42 In general, the improvement of the electrical properties of the cells may be due to the presence of a denser microstructure and larger grains as a result of lower ion bombardment energy, as previously observed. 19,28,43 Local amorphization of the grains through ion bombardment is likely caused by heavy ions through ion-induced Si bulk displacement mechanism. 41 Also, when working in capacitively coupled VHF SiH 4 / H 2 discharges in this range of pressure, previous studies 42,44 would tend to suggest that ions, the most likely responsible for this amorphization process, are the monosilicon hydride ion group SiH m + and polysilicon hydride ion groups Si nՆ2 H m + .…”
Section: E Simple Model For Ion Bombardment Energymentioning
confidence: 99%
“…[12][13][14] Second, process parameters, easily adjustable for a given reactor: power density, pressure, substrate temperature, and input gas flows. [15][16][17][18][19] Substrate morphology has been shown to be important as well. 20,21 Thus, much of the research effort is directed towards the understanding of how these externally adjustable parameters affect the internal physical plasma characteristics upon which the material quality of c-Si: H ultimately depends.…”
Section: Introductionmentioning
confidence: 99%